Energy efficient electrocoagulation using a new flow column reactor to remove nitrate from drinking water – Experimental, statistical, and economic approach. (1st July 2017) - Hashim, Khalid S.; Shaw, Andy; Al Khaddar, Rafid; Pedrola, Montserrat Ortoneda; Phipps, David
Abstract: In this investigation, a new bench-scale electrocoagulation reactor (FCER) has been applied for drinking water denitrification. FCER utilises the concepts of flow column to mix and aerate the water. The water being treated flows through the perforated aluminium disks electrodes, thereby efficiently mixing and aerating the water. As a result, FCER reduces the need for external stirring and aerating devices, which until now have been widely used in the electrocoagulation reactors. Therefore, FCER could be a promising cost-effective alternative to the traditional lab-scale EC reactors. A comprehensive study has been commenced to investigate the performance of the new reactor. This includes the application of FCER to remove nitrate from drinking water. Estimation of the produced amount of H2 gas and the yieldable energy from it, an estimation of its preliminary operating cost, and a SEM (scanning electron microscope) investigation of the influence of the EC process on the morphology of the surface of electrodes. Additionally, an empirical model was developed to reproduce the nitrate removal performance of the FCER. The results obtained indicated that the FCER reduced the nitrate concentration from 100 to 15 mg/L (World Health Organization limitations for infants) after 55 min of electrolysing at initial pH of 7, GBE of 5 mm, CD of 2 mA/cm 2, and at operating cost of 0.455 US $/m 3 . Additionally, it was found that FCER emits H2 gas enough to generate a power of 1.36 kW/m 3 . Statistically, the relationship between the operating parameters and nitrate removal could be modelled with R 2 of 0.848. The obtained SEM images showed a large number dents on anode's surface due to the production of aluminium hydroxides. Graphical abstract: Highlights: The new EC reactor, FCER, reduced the nitrate concentration by 85% within 55 min. Performance of FECR, in terms of nitrate removal, was modelled with R 2 of 0.848. FECR reduced the need for external mixing and aerating devices. FCER emits H2 gas enough to produce a power of 1.36 kW/m 3 . SEM images showed many dents on the anode due to the production of Al hydroxides.